Clinical Outcomes of the Implementation of IOP Monitoring, in and out of Office Time, to 1500 Patients—A Cohort Study - Sevasti Tsironi; Diamantis Almaliotis; Panagiota Ntonti; Georgios Sidiropoulos; Evangelia Theodoridou; Efstratios Theofrastou; Sofia Karachrysafi; Eleni Psimenidou; Anastasia Sarafi; Victoria Kapourani; Frangeskos Loizou; Elie Fadel (Vision, 2022)
Background: The aim of this study was to present the clinical outcomes of IOP monitoring in and out of office time and determine its value in our clinical practice. Material and methods: We reviewed the records of 1500 patients (glaucoma suspects or glaucoma patients), who were admitted for IOP monitoring during almost 12 years. All patients were hospitalized because their within-office-hours exams were considered inadequate and inconclusive for decision making. Results: A total of 744 patients (49.6% out of 1500) needed change of treatment. A total of 121 patients (8% out of 1500) were programmed for interventional therapy (laser or surgery). A total of 68 patients (4.5% out of 1500) were declassified as overdiagnosed and overtreated. In 250 patients (16.7% out of 1500), hidden adherence problem appeared. In 720 patients (48% out of 1500), peak IOP occurred during out-of-office hours. Conclusions: IOP phasing is a useful tool in clinical practice. In many cases with inconclusive diagnosis, as well as in patients with advanced or labile glaucomas, IOP monitoring data add complementary information, useful for decision making, and may contribute not only to diagnosis and successful IOP modulation, but also in personalized therapeutic strategy and individual patients’ motivation.